ANALISIS SISTEM PENCATATAN KEUANGAN PADA KANTOR BPK – RI PERWAKILAN PROPINSI SULAWESI – SELATAN - Yusriadi Hal (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2011)
This study aims to determine how financial recording systems and procedures are implemented at the Office of the CPC - RI Representative Sulawesi Province - South.Writing method used is descriptive analysis method that illustrates and describes the recording of Financial Systems and Procedures at the Office of the CPC - RI Representative of South Sulawesi Province.The results of this study indicate Recording system that is implemented within the scope of BPK - RI Representative Prop. South Sulawesi has been referred to the Governmental Accounting Standards and applicable regulations, BPK RI Representative of South Sulawesi in the reporting has shown an Accountability, and the reporting conducted BPK RI Representative Prop. South Sulawesi has shown a transparency to the public.